Risk of Ship Collision in the Barents Sea in 2030 - Balto, Jan Børre Hansen (UiT The Arctic University of Norway, 2014)
This thesis evaluates the risk of ship collisions in the Barents Sea in 2030 between three future scenarios; Minimum, Basis and Maximum Scenario. IWRAP Mk2 program is utilized to make the calculations. Automatic Identification System (AIS) data of 2013 is used to parameterize current traffic density, while the increased traffic in the different scenarios is derived from an analysis of multiple sources, including Rystad Petro Foresight, government documents and reports from DNV. The petroleum production in the North Sea is expected to decline, while exploration and production in the Northern part Norway is expected to increase. This will lead to that the Barents Sea will be a major contributor to oil and gas production, instead of the North Sea and the southern Norwegian Sea towards the end of 2030s. The petroleum industry is on its way north to an area that earlier mainly has been associated with high fishing activity, but may now be more dominated by larger supply vessels. This change will cause an increase in ship traffic in the area, and the probability of ship collisions may therefore be elevated. The issues discussed in this report are important for the industry, and necessary for predicting the future risk picture in the Barents Sea. It is vital to idenfity the future risk of ship collision with regards to the increase in ship traffic due to the potential consequences with respect to the harsh and vulnerable environment and lack of infrastructure in the northern part of Norway. This thesis will investigate how the probability of ship collision change, and also identify the risk of ship collisions in the Barents Sea within the different scenarios of petroleum development. There are five types of collision between ships which are taken into account in this thesis, these are; Head on collsion, crossing collsion, overtaking collsion, bend collision and merge collsion. The thesis will answer the research problems regarding to how the environmental conditions in the Barents Sea are, how the increased ...